Implementation of Supervision on the Sale of Hard Drugs in Dumai City: Normative Analysis and Preventive Strategies Based on Law No. 17 of 2023 - Suwisman, Suwisman; Harahap, Irawan; Oktapani, Silm (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the sale of prescription-only medicines should be strictly regulated by requiring a doctor’s prescription to ensure patient safety and prevent drug misuse. However, the reality in Dumai City shows that the sale of prescription-only medicines without prescriptions remains prevalent, reflecting weak supervisory functions and low legal awareness within society. This study aims to analyze the implementation of supervision over the sale of prescription-only medicines in Dumai City from a normative perspective based on Law Number 17 of 2023 on Health, while also identifying the factors influencing weak supervision and formulating effective preventive strategies. This article falls under the category of sociological legal research with a qualitative approach. The research method applied is empirical legal study, combining statutory analysis with field data obtained through observations and interviews with pharmacists, BPOM (Food and Drug Supervisory Agency), and the community. The findings conclude that weak supervision is caused by limited supervisory resources, low legal awareness, and lack of inter-agency coordination. Therefore, the necessary preventive strategies include strengthening the role of pharmacists, optimizing the functions of supervisory institutions, increasing community participation, and ensuring consistent law enforcement to achieve public health protection.